Sistem Pendukung Keputusan Pemilihan Sepeda Motor Bebek Dengan Metode Simple Additive Weighting - Ramadhan, Sandi; Mazia, Lia; Pujiastuti, Endang (Universitas Bina Sarana Informatika, 2018)
Abstract - Motorcycle is a transportation with the most fans. Various types of motorcycle is used more, one of the motorcycle cub/moped. The underbone is one that is a favorite of the riders, especially men's riders. Some motor manufacturers such as Yamaha and Honda produces underbone, with a range of offerings and offered advantages from each manufacturer. It turned out to be one more attention from consumers, they started trouble choosing which underbone that best fits their criteria. In this case, the criteria taken into consideration, including the price, the use of fuel efficient, design body, and the dimensions of the motor frame. This needs to of a Decision Support System that could helped give any information and recommendations on underbone in accordance with criteria consumers. In the development of a decision support system there is one of the models that are commonly used, namely Fuzzy MADM (Multiple Attribute Decision Making). In this research will use one method problem solving of the model , that is simple additive weighting. This method was chosen because it can determine the best alternative of some alternatives so that in accordance with the criteria referred to. In this research will be carried out the calculation of the weighted alternative that will produce the best alternative, namely the underbone elected that could be a recommendation. Keywords: Motorcycle Duck, Decision Support System, FMADM, SAW